Characterization of Kewda volatile components by comprehensive two-dimensional gas chromatography time-of-flight mass spectrometry. Issue 7 (3rd April 2017) - Nasim, Noohi; Ray, Asit; Singh, Subhashree; Jena, Sudipta; Sahoo, Ambika; Kar, Basudeba; Sandeep, I. Sriram; Mohanty, Sujata; Nayak, Sanghamitra
Abstract: Kewda ( Pandanus fascicularis Lam.) is a well known medicinal and aromatic plant. The paper aims to precisely characterize volatile constituents present in Kewda flower oil using comprehensive two-dimensional gas chromatography coupled to time of flight mass spectrometry (GCxGC-TOFMS). A total of 159 components were identified due to enhanced chromatographic separation and mass spectral deconvolution of GCxGC-TOFMS. On the basis of its chemical structure, the identified compounds were grouped into hydrocarbons, alcohols, ethers, ketones, esters, nitrogen compounds, aldehydes, acids, lactones, halides and sulfur containing compounds. Ethers were the major components. The predominant compounds identified by GCxGC-TOFMS were kewda ether, ortho -cymene and terpinen-4-ol. A database containing retention indices of compounds was created for the bi-dimensional column, thus proving to be a remarkable step for analysis of constituents using a GCxGC system. GCxGC-TOFMS separated a number of co-eluting components which were unresolved on a single GC column. Abstract :